Teaching Climate Geography with a Learner-Centered Approach – Results of a Didactic Reconstruction of the Trade Wind System - Basten, Thomas (Journal of Geography Education, 2013)
The trade wind system is an important subject of geography education. It offers an excellent opportunity for developing exemplary and transferable ideas with respect to causes of wind, adiabatic processes, coriolis deflection, etc. It can also be used to explain the climatic conditions of the tropic’s landscapes. This article contains the results of a didactic reconstruction. The scientific perspective has been analyzed by using the qualitative content analysis taking the metaphor analysis and the theory of experience-based understanding into account. The learners’ ideas of the trade wind system or related topics in previous empirical studies has been reinterpreted with the aid of theory of experience-based understanding. Moreover the learners’ conceptions of trade wind system, which were compiled in the framework of qualitative interviews with tenth-grade pupils of various German secondary schools (n=30, 18f, 12m) has been analyzed. As a result of comparing students’ and scientists’ ideas cognitive- and metacognitive-oriented guidelines were developed.